2005
DOI: 10.1002/app.21857
|View full text |Cite
|
Sign up to set email alerts
|

Boric acid recovery using polymer filtration: Studies with alkyl monool, diol, and triol containing polyethylenimines

Abstract: Three water-soluble polymers containing linear alkyl monool, 1,2-diol, and 1,2,3-triol groups, mostly on the primary amines of polyethylenimine, were synthesized, characterized, and tested for their ability to recover boric acid. The boron-binding capacities of these polymers and the backbone polyethylenimine were determined by titration, ultrafiltration, and inductively coupled plasma/ atomic emission spectroscopy analysis. At low boron concentrations, the 1,2,3-triol polymer performed better than the 1,2-dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…High reactivity of PEI [17][18][19][20][21][22] is chiefl y due to primary amino groups [10]. However, no attempts of PEI modifi cation by the Michael reaction have been reported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…High reactivity of PEI [17][18][19][20][21][22] is chiefl y due to primary amino groups [10]. However, no attempts of PEI modifi cation by the Michael reaction have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Sorbents can be jprepared both from unmodifi ed cross-linked PEI [3][4][5][6] and from the functionalized polymer [6][7][8][9][10][11][12]. PEI as a polyamine is highly active in sorption of Hg(II) (3.3 mmol g -1 [3]), Cu(II), Ni(II), Co(II), and Zn(II) ions (no less than 2 mmol g -1 [6]) and, in combination with chitosan, in sorption of Hg(II) [4], Pt(IV), and Pd(II) ions [5].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 The use of 10 B-enriched BA has been proposed as a way to (i) increase fuel cycles and fuel burn-ups, and (ii) to reduce the required concentration of BA, which is associated with stress corrosion cracking in the primary coolant loop and Zircaloy fuel-cladding corrosion. 2,3 Recent studies 4 performed by our group have shown that polyethylenimine (PEI) functionalized with 2,3-dihydroxy propyls are efficient polymer systems to recover BA because (i) they have a low average-repeat-unit (ARU) molecular weight (MW), (ii) they provide sufficiently stable boron adducts, and (iii) they are easy to synthesize.…”
Section: Introductionmentioning
confidence: 99%